2008
DOI: 10.1007/bf03033575
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic mechanism of reward-related incentive learning: Focus on the dopamine d3 receptor

Abstract: Dopamine D(3) receptors (Drd3) have been implicated in the control of responding by drug-related conditioned incentive stimuli. We review recent studies of the effects of Drd3 antagonists or partial agonists on the control of self-administration of intravenous (IV) cocaine, IV morphine and oral ethanol on reward-rich and lean schedules, in reinstatement tests, on second-order schedules and on the acquisition and expression of conditioned place preference (CPP) and conditioned motor activity. For comparison, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…These results suggest that D 3 Rs play a more important role in the expression of conditioned behaviors than in their acquisition [47,50] . Regardless of the mechanisms underlying the ineffectiveness of YQA14 at combatting the acquisition of METH-induced CPP, the present finding that YQA14 inhibits the expression of METH-induced CPP is consistent with previous reports that have shown that the blockade of D 3 Rs by SB-277011A, YQA14 or SR21502 inhibits cocaine-induced CPP [14,22,51] , cocaine and METH self-administration [12,18,21,31] , and cocaine-and METHinduced enhancement of electrical brain stimulation rewards [21,33,35] .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results suggest that D 3 Rs play a more important role in the expression of conditioned behaviors than in their acquisition [47,50] . Regardless of the mechanisms underlying the ineffectiveness of YQA14 at combatting the acquisition of METH-induced CPP, the present finding that YQA14 inhibits the expression of METH-induced CPP is consistent with previous reports that have shown that the blockade of D 3 Rs by SB-277011A, YQA14 or SR21502 inhibits cocaine-induced CPP [14,22,51] , cocaine and METH self-administration [12,18,21,31] , and cocaine-and METHinduced enhancement of electrical brain stimulation rewards [21,33,35] .…”
Section: Discussionmentioning
confidence: 80%
“…Accordingly, during the conditioning sessions, the stimuli in the chamber was associated with the METH to display the perceived appetitive. However, on the expression day, the animals that did not receive METH spent more time in the drug-paired chamber because of this incentivized learning [47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…We would hypothesize that pramipexole's activity at the D2 receptors could readily explain enhancement on attention and working memory tasks that are closely linked with the availability of DA in the PFC (Badre, 2012). In contrast, D3 receptors are most widely distributed in regions involved in reward-based learning (Beninger and Banasikowski, 2008), which might be more directly relevant for task performance on emotional decision-making measures, such as the IGT. D3 receptors are primarily expressed in the mesocorticolimbic DA pathway, and structures in this circuitry show increased activation during impulsive decision making (see Madden et al, 2010 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Our results with conditioned activity are consistent with related studies using stimulant self-administration, reinstatement, or conditioned place preference (CPP) techniques. We recently reviewed these studies (Beninger and Banasikowski, 2008) and will provide an overview of the results here. In self-administration studies, when the maintenance of responding relied heavily on conditioned stimuliin the ventral caudate and NAc core (Neisewander et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the expression test, pimozide (Beninger and Hahn, 1983;Beninger and Herz, 1986) and raclopride (Fontana et al, 1993 but see Cervo and Samanin, 1996) failed to block the expression of conditioned activity. Results suggest that D2 receptors play a more important role in acquiring conditioning than in its expression during the test phase (see Beninger and Banasikowski, 2008).…”
Section: Introductionmentioning
confidence: 99%